Antiproliferative compounds from Ocotea macrocarpa from the Madagascar dry forest1. Issue 23 (3rd June 2015) - Liu, Yixi; Cheng, Emily; Harinantenaina Rakotondraibe, L.; Brodie, Peggy J.; Applequist, Wendy; Randrianaivo, Richard; Rakotondrafara, Andriamalala; Ratsimbason, Michel; Rasamison, Vincent E.; Kingston, David G.I.
Graphical abstract: Abstract: Bioassay-directed fractionation of an antiproliferative ethanol extract of the roots of Ocotea macrocarpa (Lauraceae) afforded the new butanolide macrocarpolide A (1 ), and the two new secobutanolides macrocarpolides B (2 ) and C (3 ), together with the known butanolides linderanolide B (4 ), and isolinderanolide (5 ). The structure elucidation of all compounds was carried out based on NMR and mass spectroscopic data analyses. The absolute configurations of all compounds isolated were determined by comparison of their optical rotation values with those found in literature. Compounds1 –5 showed good antiproliferative activities against the A2780 ovarian cell line, with IC50 values of 2.57 ± 0.12 (1 ), 1.98 ± 0.23 (2 ), 1.67 ± 0.05 (3 ), 2.43 ± 0.41 (4 ), and 1.65 ± 0.44 μM (5 ), respectively.